2016
DOI: 10.1097/aog.0000000000001436
|View full text |Cite
|
Sign up to set email alerts
|

Utilization and Toxicity of Alternative Delivery Methods of Adjuvant Chemotherapy for Ovarian Cancer

Abstract: Objective Compared to conventional intravenous platinum and taxane-based chemotherapy for ovarian cancer, both intraperitoneal chemotherapy and more frequent dose-dense intravenous chemotherapy have been associated with improved survival in some studies. We examined the utilization and toxicity of these three methods of chemotherapy delivery in women with ovarian cancer. Methods We performed a population-based study and analyzed data on women with ovarian cancer who underwent primary surgery followed by plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Of course, maximal efforts should be made to eradicate the tumor as much as possible. Although recent evidences highlighted the value of precise medicine, personalized and individual therapy, along with targeted therapy for cancer patients [147][148][149][150][151]-the net health benefits (NHBs), cost-effectiveness or quality of life may reflect the relative value of treatment options in EOC [100,[152][153][154][155][156][157]. With the low risk of AEs, shortened therapeutic period, and, of most importance, working without compromising therapeutic effects-low-dose triweekly cisplatin plus dose-dense weekly paclitaxel might be associated with better NHBs, a better cost-effectiveness, and a better QOL compared to a carboplatin-based dose-dense paclitaxel regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, maximal efforts should be made to eradicate the tumor as much as possible. Although recent evidences highlighted the value of precise medicine, personalized and individual therapy, along with targeted therapy for cancer patients [147][148][149][150][151]-the net health benefits (NHBs), cost-effectiveness or quality of life may reflect the relative value of treatment options in EOC [100,[152][153][154][155][156][157]. With the low risk of AEs, shortened therapeutic period, and, of most importance, working without compromising therapeutic effects-low-dose triweekly cisplatin plus dose-dense weekly paclitaxel might be associated with better NHBs, a better cost-effectiveness, and a better QOL compared to a carboplatin-based dose-dense paclitaxel regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Intraperitoneal (IP) chemotherapy combined with systemic platinum‐based chemotherapy may confer an OS benefit for patients medically fit enough to receive adjuvant therapy . This effect is associated with the number of cycles, and toxicities are frequently related to fatigue, neuropathy, renal function, and abdominal discomfort, and are catheter‐related …”
Section: Methodsmentioning
confidence: 99%
“…This database allows for the longitudinal study of patient data and enrollment. 10,11 . The study used de-identified data and was deemed exempt by the Columbia University Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%